Terapan ELSA (English Learning Speech Assistant) sebagai Inovasi Model Pembelajaran Bahasa Inggris Pada Anak - Nurhasan, Usman; Rahmanto, Anugrah Nur; Damayanti, Retno; Nugraha, Bagas Setya Dian; Ariyanto, Rudy (Software Development, Digital Business Intelligence, and Computer Engineering, 2025)
This study aimed to evaluate the acceptance and effectiveness of an Augmented Reality (AR)-based English language learning system, ELSA, among students. Through the analysis of Technology Acceptance Model (TAM) questionnaire data and statistical tests, it was found that students had a positive perception of the usefulness and ease of use of the AR system. The use of ELSA significantly improved students' English language proficiency, particularly in vocabulary and pronunciation. Moreover, ELSA was also able to increase student motivation. However, this study identified disparities in student abilities and a lack of relevance of the material to the local context as challenges. Efforts have been made to address these issues, such as adjusting learning groups and revising materials. Overall, the results of this study demonstrate the great potential of AR in revolutionizing English language learning, especially for young learners, by providing a more interactive, personalized, and effective learning experience.